2012
DOI: 10.1002/mc.21958
|View full text |Cite
|
Sign up to set email alerts
|

Oroxylin a prevents inflammation‐related tumor through down‐regulation of inflammatory gene expression by inhibiting NF‐κB signaling

Abstract: Increasing evidence suggests that inflammatory microenvironment plays a critical role at different stages of tumor development. However, the molecular mechanisms of the interaction between inflammation and proliferation of cancer cells remain poorly defined. Here we reported the inhibitory effects of oroxylin A on the inflammation-stimulated proliferation of tumor cells and delineated the mechanism of its action. The results indicated that treatment with oroxylin A inhibited NF-κB p65 nuclear translocation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 46 publications
1
41
0
Order By: Relevance
“…From one side it has been demonstrated that a great promotion to the malignancy can come from gene adaptation to the hypoxia (Shay and Celeste Simon, 2012). From the other side it has been shown that many proinflammatory genes are overexpressed by malignant cells (Tafani et al, 2011a,b; Jin et al, 2012; Schito et al, 2012; Yao et al, 2012; De Santis et al, 2013). Bridging hypoxia adaptation and proinflammatory gene expression by cancer cells, we suggested the hypothesis that these two very complex cell responses, when sequentially activated, could be a good candidate framework to explain all the properties of the malignant phenotype.…”
Section: Introduction: a New Paradigm On Cancer Pathogenesismentioning
confidence: 99%
“…From one side it has been demonstrated that a great promotion to the malignancy can come from gene adaptation to the hypoxia (Shay and Celeste Simon, 2012). From the other side it has been shown that many proinflammatory genes are overexpressed by malignant cells (Tafani et al, 2011a,b; Jin et al, 2012; Schito et al, 2012; Yao et al, 2012; De Santis et al, 2013). Bridging hypoxia adaptation and proinflammatory gene expression by cancer cells, we suggested the hypothesis that these two very complex cell responses, when sequentially activated, could be a good candidate framework to explain all the properties of the malignant phenotype.…”
Section: Introduction: a New Paradigm On Cancer Pathogenesismentioning
confidence: 99%
“…To elucidate the observed results, we hypothesized that beta-adrenergic receptors activation shall exert a suppressive effect on NF-κβ and its inhibitor IκBα as it is well documented that NF-κB plays a key role in modulating the gene expression [37,38]. Phosphorylation of NF-κB p65 at Ser-536 was markedly reduced after beta-adrenergic receptor stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear and cytosolic protein extracts were prepared according to the modified method as described previously [50]. The cytosolic and nuclear fractions was subjected to immunoblot analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The cytosolic, nuclear extracts and whole cell lysates were prepared and subjected to Western blot analysis as described previously [50]. Bands were detected immunologically using antibodies against PI3K (1:800), Akt (1:800), p-Akt (1:800), IKKα (1:800), p-IKKα (1:800), p-IκBα (1:800), Cyclin D1 (1:800), survivin (1:800) NF-κB (1:500), phospho-p65 (1:500).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation